2019
DOI: 10.3390/nu12010004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acute Upper Respiratory Infections by Consumption of Catechins in Healthcare Workers: A Randomized, Placebo-Controlled Trial

Abstract: Catechins, phytochemicals contained mainly in green tea, exhibit antiviral activity against various acute infectious diseases experimentally. Clinical evidence supporting these effects, however, is not conclusive. We performed a placebo-controlled, single-blind, randomized control trial to evaluate the clinical effectiveness of consumption of catechins-containing beverage for preventing acute upper respiratory tract infections (URTIs). Two hundred and seventy healthcare workers were randomly allocated to high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Importantly, green tea catechins are considered as safe by FDA and already have been investigated in experimental studies in relation to some infections. Moreover, results of at least one randomized placebo-controlled study 26 strongly suggest that green tea catechins can protect against acute upper respiratory tract infections (thus, quite likely, infections induced by members of coronavirus family). Therefore, it may be expected that green tea catechins can also protect against the infection induced by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, green tea catechins are considered as safe by FDA and already have been investigated in experimental studies in relation to some infections. Moreover, results of at least one randomized placebo-controlled study 26 strongly suggest that green tea catechins can protect against acute upper respiratory tract infections (thus, quite likely, infections induced by members of coronavirus family). Therefore, it may be expected that green tea catechins can also protect against the infection induced by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect of tea consumption especially green tea on the immune system, influenza, and upper respiratory tract infections has been evaluated in previous studies (Furushima et al 2018;Furushima et al 2019;Ide et al 2017). However, there is some controversy about the effect of tea on immunity and influenza or common cold (Furushima et al 2018).…”
Section: Dietary Patternmentioning
confidence: 99%
“…The importance of phytochemicals against viral infections has been assessed. A recent randomised control trial demonstrated the effectiveness of the consumption of catechin-containing beverages for preventing acute upper respiratory tract infections (123) . Additionally, polyphenolic compound use has been suggested to manage influenza infection and its complications (124) .…”
Section: Phenolic Compoundsmentioning
confidence: 99%